Pengaruh Implementasi Kebijakan Dana Desa Terhadap Efektivitas Program Penanganan Kemiskinan Di Kecamatan Cineam Kabupaten Tasikmalaya - Leti Hastuti Nurjakiyah (Journal on Education, 2025)
This research focuses on the influence of village fund policy implementation on the effectiveness of poverty reduction programs in Cineam Sub-district, Tasikmalaya Regency. This research was conducted because data obtained indicates that poverty reduction in Cineam Sub-district sourced from Village Funds has not been effective. This is suspected to be due to a lack of policy strategies implemented by implementers. This research is expected to be beneficial for the Tasikmalaya Regency Government, especially in the Cineam Sub-district area. This research method encompasses descriptive analysis or correlational analysis. The sampling technique uses probability sampling, specifically proportionate stratified random sampling, from a total population of 131 people, resulting in a sample of 65 people. The phenomena under study are continuous variables, with data measured using a Likert scale. Data analysis employs non-parametric correlation analysis, namely Spearman's rank correlation coefficient, calculated using IBM SPSS 29.02.00 for Windows. Based on the results of the analysis and hypothesis testing, it can be seen that both variables, namely policy implementation (x) and program effectiveness (y), obtained empirical values categorized as moderate, and it is significantly proven that the sample taken applies to the entire population. Thus, it can be concluded that Ha (alternative hypothesis) is accepted and H0 (null hypothesis) is rejected, which indicates that there is an influence between the implementation of village fund policies on the effectiveness of poverty alleviation programs in Cineam District, Tasikmalaya Regency.